An Assessment of Pakistan’s Urban Policies, 1947–1997 (The Pakistan Development Review, 1996)
What public policies and programmes have been followed in dealing with mounting urban crisis in Pakistan over the past 50 years? This question has been addressed in the present article. Pakistan’s urban policies fall in three distinct phases, corresponding to evolving political and economic regimes. Yet, they show a fundamental continuity in that they have been driven by ‘plots and public works’ strategy. Pakistan has not been lacking in ‘up-to-date’ policies and programmes. Its urban policies have resulted in notable achievements and pervasive failures. The paper assesses both the achievements and shortfalls and identifies private interests that have benefited at the cost of public welfare.